Relación entre las prácticas deportivas y la convivencia escolar en estudiantes de quinto grado de educación secundaria del Colegio Nacional de Iquitos, Iquitos 2023 - Pinedo Tananta, Ray Ángelo Jesús (2025)
The purpose of this study was to determine the relationship between sports practices and school coexistence among fifth-year secondary school students at the Colegio Nacional de Iquitos Educational Institution in 2023. This was done in response to the research question: What is the relationship between sports practices and school coexistence among fifth-year secondary school students at the Colegio Nacional de Iquitos, Iquitos, in 2023? The study population consisted of 252 students from the institution. The research was non-experimental and employed a detailed correlational field methodology. Data was collected using an observational approach with two questionnaires, one for each variable, which had been previously validated by specialists. The results show that the Student's t-test statistic was 9.948, with a two-tailed significance of 0.000 and a 95% confidence level, indicating a significant relationship between sports practices and school coexistence among fifth-grade secondary school students at the Colegio Nacional de Iquitos, Iquitos, 2023, thus validating the analysis hypothesis.